2023
DOI: 10.3390/su15118753
|View full text |Cite
|
Sign up to set email alerts
|

Gen Z’s Motivations towards Sustainable Fashion and Eco-Friendly Brand Attributes: The Case of Vinted

Abstract: Vinted is a free digital sharing economy platform where individuals buy and sell second-hand apparel. It is an example of industry 4.0 that promotes an innovative and successful business model while favoring sustainable fashion consumption. Gen Z consumers are concerned about climate change and social and ethical issues. Their environmental awareness is significant. Nevertheless, their values do not always translate into sustainable consumption behavior; their role as heavy consumers in the fast-fashion market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 76 publications
1
5
0
Order By: Relevance
“…And secondly, the sample is constituted of 90.4% of female respondents, which raises the question of the gender bias of the sample. The female bias in the sample, however, is consistent with other studies on consumers' attitudes towards sustainable fashion and brand attributes in which women predominate [1]. T2: The claims the selected brand makes about their products are believable.…”
Section: Limitations Of the Studysupporting
confidence: 85%
See 1 more Smart Citation
“…And secondly, the sample is constituted of 90.4% of female respondents, which raises the question of the gender bias of the sample. The female bias in the sample, however, is consistent with other studies on consumers' attitudes towards sustainable fashion and brand attributes in which women predominate [1]. T2: The claims the selected brand makes about their products are believable.…”
Section: Limitations Of the Studysupporting
confidence: 85%
“…The fast-fashion industry is well known for having a fair share of sustainability problems [1][2][3][4]. A McKinsey report about the fast-fashion industry bluntly stated that 2019 marked a year of awakening as consumers began urging fashion brands to take a stand and address sustainability concerns [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these respondents most commonly use American online platforms such as Amazon, eBay, or Facebook Marketplace. The authors [63] confirmed that Gen Z appreciates the ecological attributes of the online second-hand platform Vinted. However, some participants claim that sustainable values are poorly represented in the advertising campaigns of the online platform Vinted.…”
Section: Discussionmentioning
confidence: 54%
“…Generation Z was born when technology was rapidly advancing, and one of their characteristics is staying up to date with various technological developments from an early age (Zis et al, 2021). Previous studies confirm that fashion trend development significantly influences the consumption patterns of Generation Z (Djafarova & Bowes, 2021;Liu et al, 2023;Manley et al, 2023;Palomo-Domínguez et al, 2023).…”
Section: Generation Z Preferencesmentioning
confidence: 99%